2006
DOI: 10.1111/j.1365-2621.2006.tb08882.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Properties of the Brazilian Cerrado Fruit Annona crassiflora (Araticum)

Abstract: Annona crassiflora, known commonly as araticum, is an exotic tropical fruit consumed mainly by native people of the Brazilian Cerrado (2nd biggest biome of Brazil). In this study, pulp, seed, and peel of slight ripe and overripe fruits were extracted using ethanol and water. The extracts showed high content of total phenols and were screening for their potential as antioxidants using the in vitro model 1,1‐ dipheniyl‐2‐picryl hydrazyl (DPPH). The ethanol extracts of peel and seeds showed IC50 of 48.82 μg/mL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 26 publications
1
33
2
19
Order By: Relevance
“…Hence, there is probably no need to be concerned about interactions between plant-based drugs and conventional medicines. The antioxidant activity of the A. crassiflora extracts in vitro (ROESLER et al, 2006) and in vivo, as demonstrated in this study, may be mediated by compounds such as ascorbic acid, caffeic acid, quinic acid, ferulic acid, xanthoxylin, caffeoyltartaric acid, caffeoyl glucose, [quercetin + hexose + pentose-H], and rutin. These compounds are widely reported as potent antioxidants and can probably explain the antioxidant activity of the A. crassiflora extracts (GÜLÇIN, 2006; …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, there is probably no need to be concerned about interactions between plant-based drugs and conventional medicines. The antioxidant activity of the A. crassiflora extracts in vitro (ROESLER et al, 2006) and in vivo, as demonstrated in this study, may be mediated by compounds such as ascorbic acid, caffeic acid, quinic acid, ferulic acid, xanthoxylin, caffeoyltartaric acid, caffeoyl glucose, [quercetin + hexose + pentose-H], and rutin. These compounds are widely reported as potent antioxidants and can probably explain the antioxidant activity of the A. crassiflora extracts (GÜLÇIN, 2006; …”
Section: Discussionmentioning
confidence: 99%
“…For the peel extract group, there was also a tendency for body gain profile reduction (-9%). In adittion, araticum seeds have approximately 16% of lipids (ROESLER et al, 2006). The lipids from the seeds were not removed before preparing the extracts and the solvent used for the extraction process also removed lipids; therefore, it is possible to affirm that the seed extract has approximately 16% of lipids as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies that included the species of Annona report excellent antioxidant activity, such as, the leaves of A. dioica (Formagio et al, 2013); leaves, bark, roots, and seedcake of A. squamosa (Baskar et al, 2007;Mariod et al, 2012;Shirwaikar et al, 2004); pulp, seeds, and peel of A. crassiflora (Roesler et al, 2006;; bark and leaves of Annona salzmannii (Costa et al, 2011(Costa et al, , 2012a; leaves of A. reticulata and A. muricata (Baskar et al, 2007;Melo et al, 2010); leaves of A. senegalensis (Ajboye et al, 2010); leaves of A. pickelii (Costa et al, 2011);and leaves of A. vepretorun (Costa et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%